ERM Report 2010. Extending flexicurity: the potential of short-time working schemes - Mandl, Irene; Storrie, Donald; Hurley, John; Mascherini, Massimiliano; Broughton, Andrea; Owczarzak, Radoslaw; Riso, Sara; Salvatore, Lidia (Luxembourg, 2010)
"In the face of recession, falling demand and the consequent slowing of production, short-time working and temporary layoff schemes have been extended (or introduced) in many Member States. These schemes, often with the aid of public funds, reduce working time, while protecting workers’ incomes and company solvency; frequently, the time spent not working is used for training instead. This report examines the practice of reduced working time across Europe, and looks in detail at how it is implemented in 10 Member States, with a view to determining the contribution that such schemes can make in implementing the common principles of flexicurity, especially in light of the broad-based consensus they enjoy among the social partners"